Long-term outcomes of hypertrophic cardiomyopathy diagnosed during childhood: results from a national population-based study - Alexander,PMA; Nugent,AW; Daubeney,PEF; Lee,KJ; Sleeper,LA; Schuster,T; Turner,C; Davis,AM; Semsarian,C; Colan,SD; Robertson,T; Ramsay,J; et al. (Circulation, 2018)
Background -Late survival and symptomatic status of children with hypertrophic cardiomyopathy (HCM) have not been well defined. We examined long-term outcomes for pediatric HCM. Methods -The National Australian Childhood Cardiomyopathy Study is a longitudinal population-based cohort study of children (0-10 years) diagnosed with cardiomyopathy between 1987 and 1996. The primary study end-point was time to death or cardiac transplantation. Results -There were 80 patients with HCM with median age at diagnosis of 0.48 (Inter-quartile range [IQR] 0.1, 2.5) years. Freedom from death/transplantation (95% confidence interval [CI]) was 86 (77-92)% one year after presentation, 80 (69-87)% at 10 years and 78 (67-86)% at 20 years. From multivariable analyses, risk factors for death/transplantation included symmetric left ventricular hypertrophy at the time of diagnosis (hazard ratio [HR] 4.20 95%CI 1.60, 11.05 p=0.004), Noonan syndrome (HR 2.88, 95%CI 1.02, 8.08, p=0.045), higher posterior wall thickness z-score (HR 1.45, 95%CI 1.22, 1.73, p<0.001) and lower fractional shortening z-score (HR 0.84, 95%CI 0.74, 0.95, p=0.005) during follow-up. Nineteen (23%) subjects underwent left ventricular myectomy. At median 15.7 years' follow-up, 27 (42%) of 63 survivors were treated with beta-blocker and 13 (21%) had an implantable cardioverter-defibrillator. Conclusions -The highest risk of death or transplantation for children with HCM is within one year post-diagnosis, with low attrition rates thereafter. Many subjects receive medical, surgical or device therapy.